2017
DOI: 10.1017/s0967199417000132
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke is associated with altered expression of antioxidant enzymes in granulosa cells from women undergoing in vitro fertilization

Abstract: This study was undertaken to evaluate whether cigarette smoke is associated with changes in the expression of antioxidant enzymes in granulosa cells of women undergoing IVF treatments. For this aim, the expression of three antioxidant enzymes (SOD1, SOD2 and catalase) in non-smokers (n = 20) and smokers (n = 20) was analyzed. There was a statistically significant overexpression of SOD2 and catalase mRNA levels in smokers in comparison with non-smokers. Cigarette smoking was associated with a lower fertilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…Experimental studies on ovarian cells retrieved from women undergoing ART demonstrated that a major ovotoxic action of smoking is oxidative stress and DNA damage in granulosa cells, which might interfere with cell maturation, binding of gonadotropins to their receptors, and oocyte fertilizing capacity [18,51]. Indeed, in smokers, a significantly increased expression of antioxidant enzymes, suggestive of smoke-induced oxidative stress, was detected in granulosa cells [52], and a significant increase in DNA damage was reported in oocyte cumulus cells [53]; moreover, morphological assessment of oocytes collected from women undergoing ART demonstrated an increased thickness of zona pellucida [54], and an increased frequency of meiotic immature diploid oocytes, probably resulting from prevention of first polar body extrusion [55]. Fetal development is a crucial phase during which germ cells complete proliferation, initiate meiosis and form the lifetime stock of primordial follicles; few studies investigated the reproductive trans-generational effects of parental smoking.…”
Section: Ovarian Reservementioning
confidence: 99%
“…Experimental studies on ovarian cells retrieved from women undergoing ART demonstrated that a major ovotoxic action of smoking is oxidative stress and DNA damage in granulosa cells, which might interfere with cell maturation, binding of gonadotropins to their receptors, and oocyte fertilizing capacity [18,51]. Indeed, in smokers, a significantly increased expression of antioxidant enzymes, suggestive of smoke-induced oxidative stress, was detected in granulosa cells [52], and a significant increase in DNA damage was reported in oocyte cumulus cells [53]; moreover, morphological assessment of oocytes collected from women undergoing ART demonstrated an increased thickness of zona pellucida [54], and an increased frequency of meiotic immature diploid oocytes, probably resulting from prevention of first polar body extrusion [55]. Fetal development is a crucial phase during which germ cells complete proliferation, initiate meiosis and form the lifetime stock of primordial follicles; few studies investigated the reproductive trans-generational effects of parental smoking.…”
Section: Ovarian Reservementioning
confidence: 99%
“…In fact, growing evidence indicates that OS levels in PCOS are significantly higher than those in healthy individuals when assessing oxidative status through circulating markers such as glutathione peroxidase, malondialdehyde, and SOD (Budani et al, 2017;Masjedi et al, 2019;Seyyed Anvari et al, 2019). High-level OS induces ROS, and elevated ROS levels in GCs promote the apoptosis of GCs to reduce IVF-ET positive pregnancy outcomes (Lai et al, 2018) (Fig.…”
Section: Mitochondrial Dysfunction Impairs Follicular Developmentmentioning
confidence: 99%
“…In addition to mitochondrial dysfunction caused by selfgenetic factors (Ding et al, 2018), external environmental factors also affect mitochondrial function. In the past 3 years, exploring the effect of environmental factors such as smoking and bisphenol A in food packaging on reproduction has received increasing attention (Budani et al, 2017;Yang et al, 2019). Disorders in ovary dynamics may also be caused by environmental toxicants and lifestyle factors, and cigarette smoking is a very common environmental toxicant and a bad lifestyle behavior that has a negative impact on the development of female ovaries (Anne Marie et al, 2013).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The results of these studies verify that melatonin has significant benefits in maintaining the function of the ovary and adnexa which normally deteriorates with age or after exposure to toxins, etc. [205,206,207,208,209]. …”
Section: The Melatonin/sirt3 Interactionsmentioning
confidence: 99%